Analysis of Road Accidents for Srinagar City (International Journal of Innovative Research in Engineering & Management, 2023)
The social, economic, and political  policies of a nation are greatly influenced by transportation  engineering. The country's financial activity is said to be  influenced by the transport sector. The creation and  assessment of road safety were accomplished in this study  through the use of an RSPQ (Road Safety Perception  Questionnaire) in two stages. The identification and choice  of road safety dimensions make up the initial phase. The  specifications and testing of conformity with traffic safety  measures make up the second stage. First-stage research  involved consulting, surveying, and interviewing a variety  of road users to determine what causes accidents in the  Srinagar city. With the assistance of Srinagar Police, the  survey stretch was taken at the bypass. The second crew  was based near Pampore, which is regarded as a hotspot  for road deaths, 20 kilometres away. For this survey,  graphs were created and data was obtained in order to  analyse and assess the traffic study in Srinagar City. The  field crew was careful not to direct the respondent during  the survey so that they would provide information in  accordance with their opinions. In addition to the  previously mentioned lengths, other places, such as bus  stops and gas stations, were used for the poll. Many road  segments from Srinagar city were selected, and a thorough  investigation was done to determine the reason  of accidents. Results on the overall number of accidents,  the unsafe acts, the types of accidents, the types of injuries,  the types of vehicles involved, and the times of accidents  were gathered. The data was examined during a four-year  period, from 2016 to 2020. The findings were compiled  and displayed graphically. A questionnaire survey was also  performed among road users to get more in-depth  information and to solicit their opinions on how to reduce  the number of accidents on the road. Following careful  study and interpretation of the results and an interview questions, it can be said that: -The year with the most  mishaps was 2018-2019, trailed by 2017-2018, and the  year with the fewest mishaps was 2019-2020.
Keywords: Roads; Accidents; Kashmir; Road safety